Community Tools for Massively Multiplayer Online Games - Christos Bouras; A Shani; Andreas Papazois; George Tsichritzis; S Ahmad; R Hamzaoui; E Perelman; G Simon; J Liu (International Journal on Advances in Networks and Services, IARIA, Vol. 4, No. 3 & 4, 2011)
One of the most attractive features of Massively Multiplayer Online Games (MMOGs) is the possibility for users to interact with a large number of other users in a variety of collaborative and competitive situations. Gamers within an MMOG typically become members of active communities with mutual interests, shared adventures, and common objectives. We present the EU funded Community Network Game (CNG) project. The CNG project provides tools to enhance collaborative activities between online gamers and offers new tools for the generation, distribution and insertion of usergenerated content in MMOGs. CNG allows the addition of new engaging community services without changing the game code and without adding new processing or network loads to the MMOG central servers. The user-generated content considered by the CNG project includes 3D objects and graphics, as well as screen-captured live video of the game, which is shared using peer-to-peer technology. We survey the state of the art in all areas related to the project and present its concept, objectives, and innovations.